The degree of using modern supporting technologies by the blind students and constraints from their point of view. - A field study in Damascus University - (Damascus University Journal of educational and Psychologyical sciences, 2021)
This study aimed to detect the degree of using modern supporting technologies by the blind students and the most important constraints that limit them of using these technologies. It  also aimed to reveal the blind students’ knowledge about the most important modern supporting technologies for them. The study was performed on a sample consisting of 65 blind students  resident in the university student house, and they were chosen randomly in an intended way, of whom were 34 males, and 31 were females, and a survey of the modern supporting technologies for the blind was designed.   The study found that the degree of using modern supporting technologies by the blind  students was medium, and the most modern technology used by the blind students was the internet in order to get information and computer programs for the blind students, and the least used technology was the modern tactile technology that transforms writing into a tactile alternative, and the color reader. The obstacles of using modern supporting technologies by the blind were in a moderate degree, and the most important of these obstacles are the lack of training courses, and the high price and the lack of availability of the modern technologies for the blind. The study also found that the degree of the blind students' knowledge of the modern technologies was low, especially audio technologies, while their knowledge of some programs for the blind was in a significant degree.
Keywords: : modern supporting technologies; the blind